Constitutive Activation of Natural Killer Cells in Primary Biliary Cholangitis - Hydes, Theresa J.; Blunt, Matthew D.; Naftel, Jennifer; Vallejo, Andres F.; Seumois, Grégory; Wang, Alice; Vijayanand, Pandurangan; Polak, Marta E.; Khakoo, Salim I. (Frontiers in Immunology, 2019)
Natural killer (NK) cells are innate immune cells that interface with the adaptive immune system to generate a pro-inflammatory immune environment. Primary Biliary Cholangitis (PBC) is a hepatic autoimmune disorder with extrahepatic associations including systemic sclerosis, Sjogren’s syndrome and thyroiditis. Immunogenetic studies have identified polymorphisms of the IL-12/STAT4 pathway as being associated with PBC. As this pathway is important for NK cell function we investigated NK cells in PBC. Circulating NK cells from individuals with PBC were constitutively activated, with higher levels of CD49a and the liver-homing marker, CXCR6, compared to participants with non-autoimmune chronic liver disease and healthy controls. Stimulation with minimal amounts of IL-12 (0.005ng/ml) led to significant upregulation of CXCR6 (p<0.005), and enhanced IFNγ production (p<0.02) on NK cells from PBC patients compared to individuals with non-autoimmune chronic liver disease, indicating dysregulation of the IL-12/STAT4 axis. In RNAseq studies, resting NK cells from PBC patients had a constitutively activated transcriptional profile and upregulation of genes associated with IL-12/STAT4 signalling and metabolic reprogramming. Consistent with these findings, resting NK cells from PBC patients expressed higher levels of pSTAT4 compared to control groups (p<0.001 vs healthy controls and p<0.05 vs liver disease controls). In conclusion NK cells in PBC are sensitive to minute quantities of IL-12 and have a “primed” phenotype. We therefore propose that peripheral priming of NK cells to express tissue-homing markers may contribute to the pathophysiology of PBC.